Analysis of Productive Waqf Management in the Context of Empowering the People by Muhammadiyah Regional Leaders, Enrekang Regency - Putriyani, Putriyani; Musdalifah, Musdalifah; Busa, Yunus; Khumairah, Ainun; Ardi, Ardi (Budapest International Research and Critics University, 2021)
Waqf has a strategic role in improving the welfare of the people if it is managed optimally. However, the use of waqf for social welfare is still very rarely done. So far, the use of productive waqf in Indonesia has not led to the economic empowerment of the people and tends to only be for the interests of worship activities and things that are commonly carried out in Indonesia such as mosques, prayer rooms, schools, graves and others. The same thing happened in Enrekang Regency. Waqf land in Enrekang Regency is divided into 5 types according to its use. The use of waqf land as a mosque dominates 80% of the total waqf land in Enrekang Regency. Followed by schools at 7%, then tombs at 6%, other social groups at 4%, and finally a prayer room at 3%. Therefore, the Regional Leadership of Muhammadiyah (PDM) Kab. Enrekang through the Waqf and Assets Council as a nazhir organization has a role in managing productive waqf that can be used to empower the people, especially the people of Enrekang Regency. Related to this problem, this research needs to be carried out to analyze the management of productive waqf by the Muhammadiyah Regional Leadership of Enrekang Regency and the empowerment of the people through the management of productive waqf, as well as the obstacles in the management of productive waqf faced by the Muhammadiyah Regional Leadership of Enrekang Regency. The type of research conducted is descriptive qualitative research. which was carried out using the methods of observation, interviews, documentation, and questionnaires with the research subject of the Muhammadiyah Regional Leadership of Enrekang Regency, specifically the Waqf and Wealth Council PDM Kab. Enrekang, wakif, and the people of Enrekang Regency. This research uses data analysis model of Miles and Huberman. The results of the study indicate that the management of waqf assets by the Waqf Council and PDM Treasurer of Enrekang Regency can be broadly said to be effective. This is supported by the results of research showing that of the total waqf land area of 41,201 m2 that is managed, 60% or 24,721 m2 have been empowered for the benefit of the community which is dominated in the form of schools/madrasah/pesantren. The remaining land that has not been utilized is 16,480 m2 or 40% of the total waqf land